Proteomic analysis of MSC‐derived apoptotic vesicles identifies Fas inheritance to ameliorate haemophilia a via activating platelet functions. Issue 7 (1st July 2022) - Zhang, Xiao; Tang, Jianxia; Kou, Xiaoxing; Huang, Weiying; Zhu, Yuan; Jiang, Yuhe; Yang, Kunkun; Li, Can; Hao, Meng; Qu, Yan; Ma, Lan; Chen, Chider; et al.
Abstract: Apoptotic vesicles (apoVs) are apoptotic cell‐derived nanosized vesicles that play a crucial role in multiple pathophysiological settings. However, their detailed characteristics, specific surface markers, and biological properties are not fully elucidated. In this study, we compared mesenchymal stem cell (MSC)‐derived apoVs and exosomes from three different types of MSCs including human bone marrow MSCs (hBMSCs), human adipose MSCs (hASCs), and mouse bone marrow MSCs (mBMSCs). We established a unique protein map of MSC‐derived apoVs and identified the differences between apoVs and exosomes in terms of functional protein cargo and surface markers. Furthermore, we identified 13 proteins specifically enriched in apoVs compared to exosomes, which can be used as apoV‐specific biomarkers. In addition, we showed that apoVs inherited apoptotic imprints such as Fas to ameliorate haemophilia A in factor VIII knockout mice via binding to the platelets' FasL to activate platelet functions, and therefore rescuing the blood clotting disorder. In summary, we systemically characterized MSC‐derived apoVs and identified their therapeutic role in haemophilia A treatment through a previously unknown Fas/FasL linkage mechanism.